2018
DOI: 10.1016/j.chemgeo.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anhydrous CaCl2 and KCaCl3 in natural inclusions by Raman spectroscopy

Abstract: Anhydrous chlorides-CaCl 2 , and KCaCl 3 (chlorocalcite) were identified as mineral inclusions in halite from the Siberian Large Igneous Province at the contact of magmatic intrusions and evaporates. Chlorocalcite was also found as daughter mineral in polyphase hypersaline inclusions. While Raman spectra of KCaCl 3 (chlorocalcite) in natural inclusions are similar to spectra of synthetic analogue, the Raman spectra of natural CaCl 2 do not correspond to the published Raman spectra of synthetic CaCl 2. Simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…These magmatic rocks of Permian-Triassic age form the Siberian Traps Large Igneous Province. Earlier studies showed that heating of the evaporate sequences resulted in the origin of Ca-bearing chloride minerals (chlorocalcite KCaCl 3 and hydrophilite CaCl 2 ) documented in NaCl deposits [23,24] and chlorocalcite in KCl deposits [25]. In this study, we document rinneite, found just in KCl deposits, intimately associated with chlorocalcite and hydrous phase (CaCl 2 Á6H 2 O) in contrast to reported Fe-free association of anhydrous chlorides [23].…”
Section: Samples Descriptioncontrasting
confidence: 49%
“…These magmatic rocks of Permian-Triassic age form the Siberian Traps Large Igneous Province. Earlier studies showed that heating of the evaporate sequences resulted in the origin of Ca-bearing chloride minerals (chlorocalcite KCaCl 3 and hydrophilite CaCl 2 ) documented in NaCl deposits [23,24] and chlorocalcite in KCl deposits [25]. In this study, we document rinneite, found just in KCl deposits, intimately associated with chlorocalcite and hydrous phase (CaCl 2 Á6H 2 O) in contrast to reported Fe-free association of anhydrous chlorides [23].…”
Section: Samples Descriptioncontrasting
confidence: 49%
“…51,53 The photoluminescence of another halide perovskite RbCaCl 3 phosphor activated with 3d elements Cu + and Mn 2+ was discussed in the reported literature. 54 The investigations of physical properties and structural stability have been done at ambient pressure 50,55,56 for experimentally synthesized Ca based alkali halide perovskite KCaCl 3 , 57 but the attempt of applying pressure on this perovskite has yet to be done. As a result, the goal of this research is to use the rst-principles calculations to examine the geometric structure, electronic, optical, and mechanical properties of non-toxic cubic halide perovskite KCaCl 3 under hydrostatic pressure and assess the results to explore the effects of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[14] A number of unusual minerals in kimberlites of Udachnaya-East pipe have been described and characterized. [15][16][17] Current work continues a series of Raman characterizations of minerals [18,19] within chloride segregations as opposed to descriptions of alkali compounds in kimberlite groundmass and secondary inclusions in olivin.…”
Section: Introductionmentioning
confidence: 99%